The show [videorecording (Blu-Ray)] - Jenkins, Mitch; Burke, Tom, 1981-; Bamber, Ellie, 1997-; Campbell-Hughes, Antonia, 1982- (Shout! Factory, 2021)
A man arrives in a haunted town in search of a person and an artifact.